Pengaruh Perputaran Modal Kerja, Likuiditas dan Pertumbuhan Penjualan terhadap Profitabilitas - Virgadinda Anindita; Elmanizar Elmanizar (Lembaga Penelitian Universitas YARSI, 2019)
This study aims to determine the effect of working capital turnover, liquidity and sales growth on profitability in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2014-2017. This study utilizes secondary data of the financial statements of food and beverage subsector companies on the Indonesia Stock Exchange in 2014-2017 collected from the official website of the Indonesia Stock Exchange. The sampling technique used purposive sampling. The samples in this study were 11 companies on the Indonesia Stock Exchange. The analysis method used ratio analysis and multiple linear regression with a significant level of 5%. The results showed that the working capital turnover, liquidity and sales growth affected significantly on profitability.